Electrochemical corrosion behaviour of Pb-free SAC 105 and SAC 305 solder alloys: a comparative study - M. Fayeka,; A.S.M.A. Haseeb,; M.A. Fazal, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Sn-Ag based solder alloy seems to be a promising lead-free solder for the application on electronic assembly. The corrosion behavior of different lead free solder alloys such as Sn-3.0Ag, Sn-1.0Ag-0.5Cu and Sn-3.0Ag-0.5Cu was investigated in 3.5% NaCl solution by potentiodynamic polarization and electrochemical impedance spectroscopy. Scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD) were used to characterize the samples after the tests. The results showed that the addition of 0.5 wt. % copper with Sn-3.0 Ag solder alloy led to a better corrosion resistance while lowering of Ag content from 3.0 to 1.0 wt. % decreased the resistance. Sn-3.0Ag-0.5Cu exhibits a better corrosion resistance in terms of increased charge transfer resistance and impedance values as well as the lowest capacitance. These characteristics signify its suitability for the application in electronic packaging.